2020
DOI: 10.1186/s12920-020-00765-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast and prostate cancers harbor common somatic copy number alterations that consistently differ by race and are associated with survival

Abstract: Background: Pan-cancer studies of somatic copy number alterations (SCNAs) have demonstrated common SCNA patterns across cancer types, but despite demonstrable differences in aggressiveness of some cancers by race, pancancer SCNA variation by race has not been explored. This study investigated a) racial differences in SCNAs in both breast and prostate cancer, b) the degree to which they are shared across cancers, and c) the impact of these shared, race-differentiated SCNAs on cancer survival. Methods: Utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Among BW, the singular TWAS-gene explained ∼1% of the variation in Proliferation score and ROR-P. Differences in the number and effect of identified TWAS-genes by race may point to factors that warrant further investigation: (1) potentially greater contribution of trans -regulation in tumor gene expression in BW, as shown previously, and (2) potential racial differences in tumor methylation and somatic alternations, which could not be accounted for in CBCS[16, 42-47].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Among BW, the singular TWAS-gene explained ∼1% of the variation in Proliferation score and ROR-P. Differences in the number and effect of identified TWAS-genes by race may point to factors that warrant further investigation: (1) potentially greater contribution of trans -regulation in tumor gene expression in BW, as shown previously, and (2) potential racial differences in tumor methylation and somatic alternations, which could not be accounted for in CBCS[16, 42-47].…”
Section: Discussionmentioning
confidence: 91%
“…First, the range of MMP1 GReX was manifold among WW than BW, suggesting sparser cis -eQTL architecture of MMP1 in BW and more influence from trans -acting signals. Potential differences in influence of germline genetics on tumor expression and ROR by race could be an artifact of divergent somatic or epigenetic factors that CBCS has not assayed [44-47]. Second, while studies generally report that MMP1 tumor expression is higher in triple-negative and Basal-like breast cancer, one study reported that MMP1 expression in tumor cells does not significantly differ by subtype [61-63].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations